Analysis of risk factors for aortic stenosis in patients with familial hypercholesterolemia - V. A. Korneva; T. Yu. Kuznetsova (Российский кардиологический журнал)
Aim. To analyze factors influencing the development of aortic stenosis (AS) in patients with heterozygous familial hypercholesterolemia (heFH).Material and methods. A total of 114 patients with heFH were examined (mean age 54,3±2,7 years, 85 men (69,1%)), of whom 10 (8,8%) had AS. FH was diagnosed according to the Dutch Lipid Clinic Network criteria. Lipid profile parameters, lipoprotein(a) (Lp(a)) level, age, family history of cardiovascular disease, smoking, hypertension (AH), hyperglycemia were analyzed. The history of coronary artery disease (CAD), myocardial infarction (MI), and ischemic stroke was taken into account. Cumulative levels of low-density lipoprotein (LDL) and non-HDL cholesterol were calculated as the total LDL-C over the patient's life, taking into account the levels achieved during lipid-lowering therapy.Results. AS development was influenced by age (odds ratio (OR) 1,1 [1,02; 1,15], p=0,009), HTN (OR 8,15 [1,50; 44,08], p=0,017), lipid profile parameters: total cholesterol (OR 2,09 [1,38; 3,10], p=0,0006; LDL-C (OR 2,8 [1,59; 4,79], p=0,0004), non-HDL-C (OR 1,012 [1,005; 1,019], p=0,003), triglycerides (OR 1,97 [1,33; 2,87], p=0,0007). Cumulative indicators also influenced the risk of AS: cumulative LDL accumulated over the years of life (OR 2,13 [1,31; 3,54], p=0,003), cumulative non-HDL-C level accumulated over life (OR 1,56 [1,01; 2,18], p=0,013), Lp(a) level (AS risk increases by 10,6 times with an increase in Lp(a) by 1 unit of measurement (1 g/l) (OR 10,5 [5,0; 21,9], p=0,0017). The presence of CAD and MI in FH increases the risk of AS (for CAD, OR 8,62 [1,07; 69,113], p=0,044; for MI, OR 3,93 [1,08; 14,36], p=0,034). The combination of MI and cerebrovascular accident increases the risk of AS by 4,94 (OR 4,94 [1,23; 19,62], p=0,021). Tendon xanthomas significantly affects the AS (OR 50,2 [6,03; 413,00], p<0,001).Conclusion. AS detected at a young age can be a manifestation of FH. The development of AS in FH is influenced by age and HTN, and following lipid factors: total cholesterol, LDL, triglycerides, as well as Lp(a) levels and cumulative indicators.